Circular RNA hsa_circ_0002360 promotes non-small cell lung cancer progression through upregulating matrix metalloproteinase 16 and sponging multiple micorRNAs - Yunting Zhang (Taylor & Francis Group, 2021)
Dysregulated circular RNAs (circRNAs) is involved in the progression of non-small cell lung cancer (NSCLC). However, the role of has_circ_0002360 (circ_0002360) in NSCLC has rarely been reported. In this study, circ_0002360 expression in NSCLC tissues and cell lines was measured with microarray data and quantitative real-time PCR (qRT-PCR). After gain-of-function and loss-of-function cell models were established, 5-bromo-2-deoxyuridine (BrdU) and transwell assays were conducted to detect NSCLC cell growth, migration and invasion. What’s more, bioinformatic analysis and dual-luciferase reporter assay were adopted to show how circ_0002360, microRNAs (miR-127-5p, miR-145-5p, miR-585-3p, and miR-758-3p) and matrix metalloproteinase 16 (MMP16) 3ʹUTR interact each other. Western blot was executed to probe the regulatory effects of circ_0002360 and these miRNAs on MMP16 protein expression in NSCLC cells. We found that circ_0002360 expression was raised in NSCLC tissues. High circ_0002360 expression predicted short overall survival time of NSCLC patients. Circ_0002360 overexpression promoted NSCLC cell proliferative, migrative, and invasive abilities, and circ_0002360 depletion worked oppositely. MiR-127-5p, miR-145-5p, miR-585-3p, and miR-758-3p were the targets of circ_0002360, and circ_0002360 could regulate MMP16 expression by competitively binding with the above miRNAs. In summary, circ_0002360 serves as a competitive endogenous RNA to raise MMP16 expressions by competitively binding to miR-127-5p, miR-145-5p, miR-585-3p, and miR-758-3p, thereby promoting NSCLC progression.